2000
DOI: 10.1002/(sici)1096-9071(200004)60:4<367::aid-jmv2>3.3.co;2-y
|View full text |Cite
|
Sign up to set email alerts
|

The NS5a gene of hepatitis C virus in patients treated with interferon-α

Abstract: Patients infected with hepatitis C virus (HCV) genotype 3 have a better response to interferon-alpha (IFN-alpha) therapy than those infected with genotype 1. There are extensive sequence differences between genotypes in the 3' half of the NS5a gene. An association between IFN-alpha response and the interferon sensitivity-determining region (ISDR) (amino acids 2209-2248) of HCV genotype 1b has been described [Enomoto et al. (1996) New England Journal of Medicine 334:771-776]. A prospective study was conducted t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…HCV anti‐viral therapy involves either α‐interferon alone, or interferon in combination with ribavirin[46], but about 60% of treated patients fail to clear the virus[47]. Generally, drug response appears to be correlated with HCV diversity during the early stages of the treatment [47–51], although not necessarily with diversity before the onset of treatment [49,52]. Diversity in non‐responders is higher than in responders, suggesting that escape mutants arise[53].…”
Section: The Genetic Diversity Of Hcvmentioning
confidence: 99%
“…HCV anti‐viral therapy involves either α‐interferon alone, or interferon in combination with ribavirin[46], but about 60% of treated patients fail to clear the virus[47]. Generally, drug response appears to be correlated with HCV diversity during the early stages of the treatment [47–51], although not necessarily with diversity before the onset of treatment [49,52]. Diversity in non‐responders is higher than in responders, suggesting that escape mutants arise[53].…”
Section: The Genetic Diversity Of Hcvmentioning
confidence: 99%
“…In the late 1990s, Enomoto et al. reported that mutations in the amino acids at positions 2209–2248 of the NS5A region of HCV were closely associated with the efficacy of IFN monotherapy; 3 however, these results proved controversial 10–22 . Very recently, a few studies have reported an association between other amino acid substitutions and the rate of SVR by the PEG‐IFN/ribavirin therapy in patients with HCV genotype 1b 7,8 .…”
Section: Introductionmentioning
confidence: 99%